6 - Book Reviews: Patrick Manning, Slavery and African Life : Occidental , Oriental , and African Slave Trades , Cambridge University Press, Cambridge, 1990, 236pp. - Zeleza, Paul Tiyambe (Africa Development, 1992)
Abstract